Resistencia a la tracción del cemento dual convencional y cemento dual autoadhesivo en endocoronas con preparación dental disminuida - Katty Pricila, Gualán Bagua (2021)
ABSTRACT This investigation was developed in order to evaluate the tensile strength of conventional dual cement and self-adhesive dual cement in endocrowns with diminished dental preparation, through an in vitro, observational, descriptive, comparative and cross-sectional study. For which 30 stumps with decreased dental preparation in CAD-CAM were milled in hybrid resin blocks (Ceramill TEMP), 30 endo-crowns were modeled with nano-hybrid resin (Neofil-Kerr) and based on the inclusion and exclusion criteria they divided the samples into 2 groups; GROUP A: 14 endo crowns with diminished dental preparation cemented with a conventional dual cement (RelyX Ultimate) and GROUP B: 14 endo crowns with diminished dental preparation cemented with a self-adhesive dual cement (RelyX U200). The specimens were subjected to tensile tests in a universal testing machine of the Centro de Fomento Productivo Metalmecánico Carrocero of the Honorable Consejo Provincial de Tungurahua. The resistance to traction force was 6.3807 ± 2.6 (MPa) for GROUP A and 3.8936 ± 1.3 (MPa) for GROUP B. Statistically significant differences were determined (p = 0.01 ) between both cements, concluding that GROUP A: Conventional dual cement (RelyX Ultimate) presented greater resistance to tensile forces when cementing endo-crowns with decreased dental preparation. Keywords: Tensile strength, conventional dual cement, dual self-adhesive cement, endocrowns.